2014
DOI: 10.5430/jha.v3n4p92
|View full text |Cite
|
Sign up to set email alerts
|

Missed appointments at maternal healthcare clinics in primary healthcare centres in Riyadh city: reasons and associated factors

Abstract: Background: The issue of missed appointments at maternal healthcare clinics in primary healthcare centers (PHCCs) has received increasing attention in recent years. The significant relationship between missed appointments and access to maternal healthcare has been recognized around the world. Missed appointments have serious health and economic consequences for women seeking maternal healthcare at PHCCs. Objectives:The objectives of this research were 1) to critically explore the reasons for and socio-demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
(52 reference statements)
2
14
0
Order By: Relevance
“…More than, 90% of the mothers were positive about getting reminders for their PNC appointment. This finding was in line with several studies done in other places [40,[50][51][52][53]. This finding was higher compared to study done in Ilorin Nigeria, which showed 69% acceptance of reminders for immunization service [54].…”
Section: Discussionsupporting
confidence: 90%
“…More than, 90% of the mothers were positive about getting reminders for their PNC appointment. This finding was in line with several studies done in other places [40,[50][51][52][53]. This finding was higher compared to study done in Ilorin Nigeria, which showed 69% acceptance of reminders for immunization service [54].…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to the low level of awareness of the impact of missed appointment reported in a study in maternal healthcare clinics in Saudi Arabia [23]. Improved and continuous patient education on the importance of follow-up visits will significantly influence adherence to aspect of disease management as well as improve selfmanagement practices and treatment outcomes [24].…”
Section: Discussionsupporting
confidence: 71%
“…As the study was exploratory and novel in terms of a lack of previous research in this region on this topic, the preferred sample size was calculated by examining the sample size of the one published quantitative research study examining reasons for antenatal care attendance in Saudi Arabia (n = 200) 10 and a sample size power calculation. Based on the number of women who on average give birth each year in the selected hospitals, the inclusion and exclusion criteria and the period of data collection it was determined that a sample size of at least 235 was required to give sufficient power to the study at 95% confidence and 5% margin of error.…”
Section: Participantsmentioning
confidence: 99%
“…Understanding why women are not attending ANC in Saudi Arabia is a government priority but research exploring this issue is sparse. For example, one interview-based study identified a perceived lack of respectful communication from staff and clinics that were not well equipped 10 Conversely, other research in the area has simply focussed on exploring whether mothers value care rather than barriers to attendance. Notably, each study examining this issue concluded that mothers did value care, suggesting further barriers are likely to be preventing attendance [11][12][13] In a previous study we conducted qualitative interviews with pregnant and mothers who had missed at least one ANC appointment and health professionals working in ANC to understand perceptions on why appointments were missed 14 .…”
Section: Introductionmentioning
confidence: 99%